2001
DOI: 10.1097/00004032-200110000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Parameter Uncertainties Within the Icrp 66 Respiratory Tract Model

Abstract: Risk assessment associated with the inhalation of radioactive aerosols requires as an initial step the determination of particle deposition within the various anatomic regions of the respiratory tract. The model outlined in ICRP Publication 66 represents to date one of the most complete overall descriptions of not only particle deposition, but of particle clearance and local radiation dosimetry of lung tissues. In this study, a systematic review of the deposition component within the ICRP 66 respiratory tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 25 publications
0
27
0
7
Order By: Relevance
“…First, due to the localization, mostly in the deeper regions of the respiratory tract of humans, target cells may not easily be reached by avian influenza viruses transmitted via the respiratory route of transmission. Only the smallest droplets deposit in the deeper regions of the human respiratory tract, 69 and the extent to which avian influenza virus particles can be transported and released in association with such droplets, and attain the deeper regions of the human respiratory tract remains unknown. Furthermore, the muco-ciliary escalator may trap and remove influenza virus particles depositing along the airways toward the upper regions of the respiratory tract, 70 preventing them from reaching their target cells.…”
Section: Do Not Distributementioning
confidence: 99%
“…First, due to the localization, mostly in the deeper regions of the respiratory tract of humans, target cells may not easily be reached by avian influenza viruses transmitted via the respiratory route of transmission. Only the smallest droplets deposit in the deeper regions of the human respiratory tract, 69 and the extent to which avian influenza virus particles can be transported and released in association with such droplets, and attain the deeper regions of the human respiratory tract remains unknown. Furthermore, the muco-ciliary escalator may trap and remove influenza virus particles depositing along the airways toward the upper regions of the respiratory tract, 70 preventing them from reaching their target cells.…”
Section: Do Not Distributementioning
confidence: 99%
“…The U S ratios between our and DCAL results are in the range of 0.995-1.001. Bolch et al (2001Bolch et al ( , 2003 analyzed the influences of uncertainties of particle deposition and clearance parameters on the nuclear transformations in the ICRP HRTM. It is found that in all the regions of the respiratory tract for an adult male at light exertion, uncertainties in particle deposition fractions are distributed only over a range of about a factor of 2-4 for particle sizes between 0.005 and 0.2 mm.…”
Section: Quality Assurance and Uncertainty Of Dose Coefficientmentioning
confidence: 99%
“…Bolch and coworkers (Bolch et al, 2001Farfan et al, 2003;Huston et al, 2003) published a series of papers addressing uncertainties associated with predictions of the HRTM as discerned from parameter uncertainty analysis. They reviewed the original data on which 69 default parameter values of the HRTM were based, selected subjective distributions that they referred to as "probability distributions" for these parameter values, and propagated these distributions through the HRTM to derive distributions of lung dose.…”
Section: Detailed Parameter Uncertainty Analysis For Inhaled Puo 2 Ormentioning
confidence: 99%
“…They reviewed the original data on which 69 default parameter values of the HRTM were based, selected subjective distributions that they referred to as "probability distributions" for these parameter values, and propagated these distributions through the HRTM to derive distributions of lung dose. Uncertainties in the following model predictions were addressed in separate papers: particle deposition (Bolch et al, 2001) ; and identification of the input parameters to which their dose estimates for inhaled 239 PuO 2 were most sensitive . For "typical exposure scenarios" involving these radionuclides, the ratio of their derived 95% to 5% confidence levels was on the order of 8-10 for particles diameters 0.1-1.0 μm.…”
Section: Detailed Parameter Uncertainty Analysis For Inhaled Puo 2 Ormentioning
confidence: 99%
See 1 more Smart Citation